P10.12.A CDK12/CDK13 inhibition disrupts a transcriptional program critical for glioblastoma survival. (5th September 2022) - Lier, S; Rein, I; Lund, S; Lång, A; Lång, E; Meyer, N; Dutta, A; Anand, S; Nesse, G; Johansen, R; Klungland, A; Rinholm, J; et al.
Abstract: Background: Glioblastoma multiforme (GBM) is the most prevalent and aggressive malignant tumor of the central nervous system. With a median survival of only one year, GBM patients have a particularly poor prognosis, highlighting a clear need for novel therapeutic strategies to target this disease. Transcriptional cyclin-dependent kinases (CDK), which phosphorylate key residues of RNA polymerase II (RNAPII) C-terminal domain (CTD), play a major role in sustaining aberrant transcriptional programs that are key to development and maintenance of cancer cells. Material and Methods: We used pharmacological inhibition and genetic ablation to study effects of CDK12/CDK13 depletion on the proliferatory and migratory capacity of GBM cells and mouse xenografts. SLAM-seq, CUT&RUN and cell cycle assays were used to study the mechanistic effects of CDK12/CDK13 depletion in GBM cells. Results: CDK12/CDK13 depletion markedly reduced the proliferatory and migratory capacity of GBM cells, as well as in vivo growth. CDK12/CDK13 inhibition potentiated existing chemotherapeutic treatments. Mechanistically, inhibition of CDK12/CDK13 leads to a genome-wide abrogation of RNAPII CTD phosphorylation, which in turn disrupts transcription and cell cycle progression in GBM cells. Conclusion: These results provide proof-of-concept for the potential of CDK12 and CDK13 as therapeutic targets for GBM.